2021
DOI: 10.1007/s10212-021-00568-8
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring students’ science motivation across grade levels and the role of inductive reasoning in science motivation

Abstract: The purpose of this study is to explore students' motivation towards science learning at different grade levels and to investigate whether inductive reasoning can contribute to an explanation of science motivation. The study conducted a cross-sectional assessment in six public schools in Vietnam with a total population of 813 students from the 5th, 7th, 9th, 10th and 11th grades. Students completed instruments in either paper-and-pencil or online administration modes. An adapted science motivation questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Numerous studies have highlighted the importance of student motivation in learning. Most research has shown that positive motivation to learn improves students' academic achievement during their school years and is also one of the most important factors for their future success (Riswanto & Aryani, 2017;Van Vo & Csapó, 2021). Studies in educational research have frequently examined students' interests, motivations, and attitudes toward science (Drymiotou et al, 2021;Osborne et al, 2003;Potvin & Hasni, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have highlighted the importance of student motivation in learning. Most research has shown that positive motivation to learn improves students' academic achievement during their school years and is also one of the most important factors for their future success (Riswanto & Aryani, 2017;Van Vo & Csapó, 2021). Studies in educational research have frequently examined students' interests, motivations, and attitudes toward science (Drymiotou et al, 2021;Osborne et al, 2003;Potvin & Hasni, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Science motivation affects students' achievementrelated behaviors (Badru & Owodunni, 2021;Liou, 2021;Schumm & Bogner, 2016b;Singh et al, 2002;Wicaksono et al, 2018). Some aspects of motivation are influenced by personal characteristics, while others are influenced by direct and indirect contacts in family, school, and society (Van Vo & Csapó, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students are expected to demonstrate these abilities and skills to meet the demands of future jobs. IR and scientific reasoning in the CVS are closely tied to problem-solving and play an important role in learning core school disciplines (e.g., Adey & Csapó, 2012;Chen & Klahr, 1999;Van Vo & Csapó, 2021a, 2021b. Modern society is under ever greater pressure to deal with more information in a shorter amount of time.…”
Section: Implications In Science Educationmentioning
confidence: 99%
“…Children's activities in school and family environments have an influence on science motivation (SM) and achievement (Pintrich & Schunk, 2002). For instance, experiences in a school environment (Bathgate & Schunn, 2017;Hernesniemi et al, 2020) and parental involvement in schooling (Fan et al, 2012;Gonzalez-DeHass et al, 2005;Van Vo & Csapó, 2021a) have a positive effect on children's motivation in learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation